2017
DOI: 10.1086/694421
|View full text |Cite
|
Sign up to set email alerts
|

Opsin Expression in the Central Nervous System of the Mantis Shrimp Neogonodactylus oerstedii

Abstract: Visual pigments, each composed of an opsin protein covalently bound to a chromophore molecule, confer light sensitivity for vision. The eyes of some species of stomatopod crustaceans, or mantis shrimp, can express dozens of different opsin genes. The opsin diversity, along with spectral filters and unique tripartite eye structure, bestow upon stomatopods unusually complex visual systems. Although opsins are found in tissues outside typical image-forming eyes in other animals, extraocular opsin expression in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Following our observations of light-induced behaviors in eyeless mantis shrimp, and the identification of a photosensitive ventral eye, we investigated the expression patterns of opsins potentially used to produce light sensitive visual pigments in mantis shrimp extraocular photoreceptors. Our previous transcriptomic analyses revealed that four opsin transcripts—one middle-wavelength-sensitive (MWS) and three long-wavelength-sensitive (LWS) opsins—are expressed in the CG of N. oerstedii 21 . Therefore, we labeled mantis shrimp eyestalk and CG tissues using gene-specific in situ probes to visualize the expression of these four identified opsin transcripts.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Following our observations of light-induced behaviors in eyeless mantis shrimp, and the identification of a photosensitive ventral eye, we investigated the expression patterns of opsins potentially used to produce light sensitive visual pigments in mantis shrimp extraocular photoreceptors. Our previous transcriptomic analyses revealed that four opsin transcripts—one middle-wavelength-sensitive (MWS) and three long-wavelength-sensitive (LWS) opsins—are expressed in the CG of N. oerstedii 21 . Therefore, we labeled mantis shrimp eyestalk and CG tissues using gene-specific in situ probes to visualize the expression of these four identified opsin transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…The NoLWS1 opsin riboprobe labels the dorsal and ventral hemispheres of the retina, likely labeling transcripts of No14, an opsin transcript sequence that was isolated from the eye of N. oerstedii 18 and has the same 3′ untranslated region (3′-UTR) sequence (see ref. 21 for sequence alignment). In the CG, NoMWS1 and NoLWS3 opsin transcripts are coexpressed in the ventral eye, and NoLWS1 and NoLWS2 opsin transcripts are expressed in cell bodies, including those in the olfactory lobe (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations